Enotni naslov - Tratar, Patricija (Knjižnica, 2005)
The goal of this work is the comparison of rules about forming and using uniform titles in PPIAK, AACR2, RICA and RAK-WB. Uniform title is the title which we form for works that are published under different titles. It has been used more widely and it has been more clearly articulated since its appearance in Panizzi's rules. The comparison between different national cataloguing rules shows that all four cataloguing rules arose from Paris principles. Their differences originate in different needs of cataloguing experts, users and characteristics of particular state. On the first meeting of experts for an international cataloguing code held in Frankfurt in 2003, they have compared the rules of collaborating states and outlined guidelines for forming an international cataloguing code.
Keywords: katalogizacija; bibliografski opis; enotni naslov; PPIAK; AACR2R; RICA; RAK-WB